Some notes on poem VII of Trilce - López Maguiña, Santiago (2023)
In this text, we propose a reading that does not pretend to interpret or find some hidden sense or meaning. We rehearse some translations of the language of otherness of Trilce’s texts. Our main objective is to assemble the figurative composition of the text, which can open the way for a wider assemblage. In this way, we have found some directions of meaning and traces that aim to form icons that figurative certain categories: the legal vs. the illegal, the just and the unjust, rascality and circumspection, liberation and confinement, alongside those of mobility and immobility, change and stagnation, linearity and circularity, ceremoniality and routine, innovation and continuity, prudence and risk, the rural and the urban.